Stephen A. Ross, mentor : influence through generations - Grinblatt, Mark (McGraw-Hill/Irwin, 2008)
"Collection of reprinted articles by former students dedicated to Professor Stephen A. Ross."
Keywords: Ross, Stephen A., -- 1944-; ekonomové -- Spojené státy americké -- 20.-21. století; ekonomie; economists -- United States -- 20th-21st centuries; economics; jubilejní publikace; sborníky; jubilee books; papers of several authors